2018
DOI: 10.1108/maj-09-2016-1438
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance compliance and accrual earnings management in eastern Africa

Abstract: Purpose The purpose of this paper is to examine whether compliance with corporate governance (CG) requirements has constrained earnings management (EM) for companies listed in Kenya and Tanzania. Design/methodology/approach The sample comprises of 48 companies listed on the Nairobi Stock Exchange and the Dar es Salaam Stock Exchange. The data are collected from annual reports over the period 2005-2014, a total of 480 firm-year observations. Panel data models are used in the analyses. Findings The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 68 publications
(92 reference statements)
3
54
0
3
Order By: Relevance
“…While (Houqe et al, 2011; Fodio et al, 2013; Jessica, 2020) found a significant positive influence of BS on EQ and favours the larger board for less earning manipulation and good EQ. However (Khafid & Arief, 2017;Waweru & Prot, 2018;Mousa & Desoky, 2019) showed no association between the BS and EQ. Hence the literature has varying results, so based on such association, the following hypothesis is proposed:…”
Section: Dividend Policy and Earnings Qualitymentioning
confidence: 97%
See 2 more Smart Citations
“…While (Houqe et al, 2011; Fodio et al, 2013; Jessica, 2020) found a significant positive influence of BS on EQ and favours the larger board for less earning manipulation and good EQ. However (Khafid & Arief, 2017;Waweru & Prot, 2018;Mousa & Desoky, 2019) showed no association between the BS and EQ. Hence the literature has varying results, so based on such association, the following hypothesis is proposed:…”
Section: Dividend Policy and Earnings Qualitymentioning
confidence: 97%
“…All these researches were performed in developed economies of the world. Furthermore, (Epps & Ismail, 2009; Waweru & Riro, 2013; González & García-Meca, 2014; Hassan & Farouk, 2014;Waweru & Prot, 2018) also found an association between CG and the EQ. These studies argued that the corporate failures around the world were due to earnings manipulation, and it happened in the companies that had weaker corporate governance mechanism, so the management, in turn, can easily mislead the investors by presenting the manipulated earning and the false earning quality (Epps & Ismail, 2009).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…had earlier on encouraged researchers to focus their attention on investigating the relationships among IFRS, accounting quality and earnings management in oriental and non-English-speaking countries such as China. This call has trickled down to Africa, with emerging studies on earnings management and financial reporting quality in recent years (see for example, Amidu et al, 2016;Amidu & Kuipo, 2015;Rabin, 2016;Rabin & Negash, 2007;Uwalomwa et al, 2014;Waweru & Ntui, 2018;Waweru & Riro, 2013;Yiadom, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notable cases of corporate failure include Uchumi Supermarkets, in 2006, andCMC Kenya Ltd., in 2012. The main reasons attributed to these corporate failures are their inefficient boards and the use of debt in the capital structure (Waweru and Prot, 2018). Although Kenya Capital Authority has enacted and implemented the corporate governance guidelines, there remains a need to determine whether governance mechanisms enhance effective decision making in Kenya, particularly with regard to capital structure.…”
Section: Introductionmentioning
confidence: 99%